2019
DOI: 10.1093/ckj/sfz021
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with parathyroid hormone control in haemodialysis patients with secondary hyperparathyroidism treated with cinacalcet in real-world clinical practice: Mimosa study

Abstract: BackgroundSecondary hyperparathyroidism (SHPT) is frequent in haemodialysis (HD) patients. Oral cinacalcet-hydrochloride (HCl) decreases parathyroid hormone (PTH); however, real-life PTH data, according to Kidney Disease: Improving Global Outcomes (KDIGO) guidelines, are still lacking. Our goal is to assess the percentage of cinacalcet-HCl-treated HD patients with controlled SHPT (PTH <9× upper limit of the normal range) after 12 months (M12) of treatment.MethodsThis is a retrospective observational study in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
1
16
1
2
Order By: Relevance
“…While direct comparisons of etelcalcetide to cinacalcet or no calcimimetic therapy were beyond the scope of the current manuscript, they are investigated in a recent systematic review and meta-analysis by Palmer et al [38] who found that etelcalcetide was more effective at lowering PTH than cinacalcet, but with an increased risk of hypocalcemia. A large observational study of cinacalcet initiators in France [39] showed that the proportion of patients with PTH out of target range (>9x upper limit) after 12 months was 41%, compared to 26% with PTH >600 pg/mL after 12 months in our study of etelcalcetide initiators. In both studies, however, the likelihood of PTH in-target after 12 months was highly dependent on baseline SHPT severity, suggesting the potential benefit of treating SHPT at earlier stages.…”
Section: Discussioncontrasting
confidence: 59%
“…While direct comparisons of etelcalcetide to cinacalcet or no calcimimetic therapy were beyond the scope of the current manuscript, they are investigated in a recent systematic review and meta-analysis by Palmer et al [38] who found that etelcalcetide was more effective at lowering PTH than cinacalcet, but with an increased risk of hypocalcemia. A large observational study of cinacalcet initiators in France [39] showed that the proportion of patients with PTH out of target range (>9x upper limit) after 12 months was 41%, compared to 26% with PTH >600 pg/mL after 12 months in our study of etelcalcetide initiators. In both studies, however, the likelihood of PTH in-target after 12 months was highly dependent on baseline SHPT severity, suggesting the potential benefit of treating SHPT at earlier stages.…”
Section: Discussioncontrasting
confidence: 59%
“…Current guidelines recommend active vitamin D prescription and calcimimetics in order to maintain PTH levels in the recommended ranges in HD patients. In real life, observational studies showed that calcimimetic prescription is less than expected, and that treatment can be challenging to achieve and to maintain in the long term, partly due to gastrointestinal intolerance [ 43 ]. Moreover, reimbursement criteria do not necessarily match with guidelines, and local committees (such as in Sweden and Australia) may not recommend calcimimetic use except in patients at high risk, due to the inconclusive results of the EVOLVE (EValuation Of Cinacalcet Hydrochloride Therapy to Lower CardioVascular Events) trial [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…спостереження цільовий рівень ПТГ був досягнутий лише у 10,4% пацієнтів. Це корелює з даними дослідження Jacques Rottembourg зі співавторами [12]. В цьому дослідженні проводилася ретроспективна оцінка показників мінерального обміну у гемодіалізних хворих з ВГПТ, які лікувалися цинакальцетом.…”
Section: Complete Censoredunclassified